SAFEty assessment of a REdirection process after TRIage (SAFE RETRI) by a triage nurse in an emergency department: a monocentric cohort study (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: As emergency department consultations rise across Europe, patients must be guided to obtain appropriate care at the right time and place.In Switzerland, the absence of a unique health number that would enable the avoidance of emergency services through telephone medical advice, and the shortage of general practitioners, redirecting low-severity patients from the emergency department before medical consultation to other healthcare facilities could help reduce emergency department overload. This study assessed the safety of a newly implemented redirection process by examining the rate of unexpected returns to any healthcare facility.METHODS: This monocentric cohort study included patients aged 18 or older who presented to the emergency department of a regional hospital in Switzerland between 1 January and 31 May 2023 and who accepted redirection before medical consultation. Patients were identified from our electronic medical registry and retrospectively enrolled after telephone interviews. The primary outcome was the rate of unexpected returns to any healthcare facility within 2 days of redirection. The secondary outcomes were the rate of returns within 7 days, hospital admissions, and patient satisfaction.RESULTS: Among 16,362 patients who came to the emergency department during the study period, 688 (4%) were redirected. A total of 321 patients were included in the final analysis after telephone interviews. The rate of unexpected returns to any healthcare facility after redirection was 4% within 2 days and 16% within 7 days. The rate of returns to any hospital was 1.2% within 2 days and 4.7% within 7 days after redirection. Six patients (2%) required hospitalisation, and no fatalities were reported. The mean satisfaction score was 3.9/5 (standard deviation [SD] = 1.1) for triage experience, 4.4/5 (SD = 1) for care received in partner clinics, and 3.7/5 (SD = 1) for the redirection process.CONCLUSION: The rate of unexpected returns to any healthcare facility after redirection was 4% within 2 days and 16% within 7 days. The implementation of this protocol appeared to provide safe redirection to nearby clinics for redirected low-acuity patients. Satisfaction with care received in partner clinics was high, although it was lower for the redirection process and triage experience.